Kepemimpinan Berbasis Nilai Dalam Mengembangkan Mutu Pendidikan Di Pesantren Amanah Tahfiz Sunggal Deli Serdang (Study Kasus - Minar Adelina Tanjung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research aims to identify and analyze value-based leadership in developing the quality of education at the Amanah Tahfiz Sunggal Islamic boarding school, Deli Serdang. Using qualitative research methods, research techniques using observation, interviews, and documentation. Data analysis using data reduction, data presentation, and conclusions. The results of the research are values-based leadership at the third amanah Islamic boarding school, beginning with planning which divides its personnel into certain sections to improve the quality of education and dividing the main tasks and functions in the form of improving the quality of education and moving them to achieve the plan. The principal's efforts in carrying out his main role as a leader, manager, entrepreneurship development, and supervisor well, in addition to other roles. As someone who has values ​​trying to improve the quality of education, working hard and intelligent, creative, innovative, committed, and trying to set an example for his school members. Principal leadership to improve the quality of education has been carried out, including coaching and collaboration with all school members, increasing the participation of school members, the community, and stakeholders, establishing cooperation with related parties, conducting guidance and training, inviting resource persons, deepening material, raising funds, social services, promotions, and others. In conclusion, value-based leadership at the Amanah Tahfzd Islamic Boarding School is in accordance with the characteristics of value-based leadership in terms of accountability, professionalism, transparency, and communicativeness, which is a leadership concept that compares various aspects related to values ​​in relationships between members of the organization, cooperation with basic values-based organizations high commitment and serving the school community based on organizational values. Keyword: Value-Based Leadership in Developing Education Quality